Isolasi dan identifikasi dengan gen 16s rRNA bakteri endofit dari tanaman pepaya (Carica papaya L.) serta uji aktivitas antibakterinya - Irwandi; Lola Azyenela; Hera Purnama Sari; Epi Supri Wardi; Diza Sartika (Journal of Pharmaceutical and Sciences, 2023)
Endophytic bacteria live symbiotically in host plant tissues and can produce the same bioactive compounds as their host plants, including antibacterial agents. This study aimed to isolate and test the antibacterial activity of endophytic bacteria from the Carica papaya plant and to carry out molecular identification using the 16S rRNA gene against bacterial isolates with the most excellent antibacterial activity. A total of six isolates of endophytic bacteria were successfully separated through the purification process. Through microscopic identification using gram staining, all endophytic bacterial isolates belong to gram-positive bacteria. The results of the antibacterial activity test showed that the six isolates of papaya plant endophytic bacteria could cause the growth of Escherichia coli bacteria but not against Staphylococcus aureus bacteria. The average diameter of the inhibition zone against Escherichia coli bacteria is as follows: RB1: 9.35 mm; RB2: 9.4mm; RB3: 9.15mm; CB1: 9.1mm; CB2: 9.2mm; CB3: 8.8mm; FB1: 8.45mm; FB2: 8.75mm; and FB3: 8.6mm. All papaya plant endophytic bacterial isolates had an inhibition zone categorized as weak. Bacterial isolate RB2, which has the most excellent antibacterial activity, is identified molecularly as Bacillus cereus.